Fructus gardeniae ameliorates anxiety-like behaviors induced by sleep deprivation via regulating hippocampal metabolomics and gut microbiota - Liu, Dong; Wang, Qianfei; Li, Ying; Yuan, Zhenshuang; Liu, Zhiliang; Guo, Junli; Li, Xin; Zhang, Weichao; Tao, Yulei; Mei, Jianqiang (Frontiers in Cellular and Infection Microbiology, 2023)
Fructus Gardeniae (FG) is a traditional Chinese medicine and health food with over 2000 years of application throughout Chinese history and is still widely used in clinical Chinese medicine. FG has a beneficial impact on anxiety, depression, insomnia, and psychiatric disorders, however, its mechanism of action requires further investigation. This study aimed to investigate the effects and mechanisms of FG on sleep deprivation (SD)-induced anxiety-like behavior in rats. A model of SD-induced anxiety-like behavior in rats was established by intraperitoneal injection of p-chlorophenylalanine (PCPA). This was accompanied by neuroinflammation and metabolic abnormalities in the hippocampus and downstream disturbance of intestinal flora. However reduced SD-induced anxiety-like behavior and decreased levels of pro-inflammatory cytokines including TNF-α and IL-1β were observed in the hippocampus of rats after 7 days of FG intervention. In addition, metabolomic analysis demonstrated that FG was able to modulate levels of phosphatidylserine 18, deoxyguanylic acid, sn-glycero-3-phosphocholine, betaine, and other metabolites in the hippocampus. The main metabolic pathways of hippocampal metabolites after FG intervention involve carbon metabolism, glycolysis/gluconeogenesis, pentose phosphate, and glycerophospholipid metabolism. 16S rRNA sequencing illustrated that FG ameliorated the dysbiosis of intestinal flora in anxious rats, mainly increased the abundance of Muriaculacea and Lactobacillus, and decreased the abundance of Lachnospiracea_NK4A136_groups. In addition, the correlation analysis demonstrated that there was a close relationship between hippocampal metabolites and intestinal flora. In conclusion, the inhibition of inflammation and the regulation of hippocampal metabolites and gut microbiota composition may be important mechanisms by which FG ameliorates anxiety behavior in sleep deprived rats.